Upaya Preventif Malaria Melalui Pembentukan Sukarelawan “Malaria Guard Kembang Ayun” (Margaku) dengan Pemanfaatkan Tanaman Serai Wangi (Cymbopongon nardus. L., rendle) di Desa Kembang Ayun. - Irawan, Putra Adi (Poltekkes Kemenkes Bengkulu, 2023)
Abstract The case of malaria that occurred again in the village of Kembang Ayun is still a scourge that was thwarted by Kab. Central Bengkulu was canceled as a complete malaria area. This is a potential that needs to be carried out by the Village Partner Development Service Program as a preventive effort in dealing with malaria transmission and to support local government programs to become complete malaria areas. Community service is carried out as a form of transfer of knowledge and technology regarding the benefits of citronella in fighting malaria. There was a significant difference (p=0.00) in the level of community understanding before and after the activity. Keywords: Malaria; Cymbopogon nardus; Prevention